Cannabis and performance - Lemery, N.; Poujade, B.; Barthelemy, J. C.; Garet, M. (First international symposium sciences and practices in swimming, 2006)
Cannabis is considered as a doping substance by the International Olympic Comitee (IOC) and by many national and international sports federations. The use of such a drug is increasing in the whole population including athlethes and , among them, mainly the young ones who are at their best. Many studies prove that most of its physical and psychological effects have a harmful impact on performance. However, most of these informations are collected from animal models. That is why it would be worth carrying out transversal and longitudinal studies on human beings during a sporting competitive event so as to make young sporting people aware of the effects of cannabis.